Iterative Integral Equation Method for Efficient Computation of Multiple Scattering - Xiaoyan Zhang; Zhiwei Liu; Shan He; Yingting Liu; Yueyuan Zhang (Institute of Advanced Engineering and Science, 2014)
An iterative integral equation method (IEM) is proposed for calculation of the electromagnetic (EM) scattering field from geometries with multiple reflections, such as rough surface, dihedral and trihedral. The first reflection is computed by physical optics and the coupling effects are computed by integral equations. The average size of the triangular meshes used in the proposed method is a constant value while that in method of moment is a linear function of wavelength. As a result, compared with method of moment, the proposed method will lead to less number of unknowns for electrically large geomety. Accordingly, this method is more efficient and suitable for fast computation of scattering from electrically large geometry. Further more, when compared with high frequency asymptotic method, the proposed method is more accurate. The numerical results demonstrate that this method is accurate for computation scattering with multiple reflections and efficient for electrically large object. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4932